Public rights and freedoms in contemporary Islamic thought - Siti Fatimah, Salleh; Mostafa Hassan, Mohamed El Khayat; Dima F.T., Abulatefa (2019)
Pluralism and diversity are considered as one of the laws (Sunan) of God in His creation. It is natural that Islam establish all the rules, and provide all the necessary requirements in order to protect this pluralism and diversity whereby God created us distinct in languages and colors. For this reason, Islam derived its strength and greatness from the liability of these legislations, concepts and principles for application on the ground, and from their being within the bounds of the limited human capacity and energy. The problem of the research lies in the original differences which make variance obvious between Islam and the contemporary political thought in determining the rights and the public freedoms. The researcher aims from this study to clarify the most important rights and freedoms in the contemporary Islamic thought and to discuss the difference between the Islamic epistemological model and the material epistemological model, and also to show the differences between the Islamic conceptualization and the Western conceptualization concerning the rights and the freedoms. In order to achieve the aim of this study, the researcher used the descriptive analytical methodology. The study reached the following results: that the human freedom should be committed to the horizons of Shari’a (Muslim religious law), the limits of God, and that Islam considers freedom as being necessary for humanity in general and not only for the Muslim person alone. Equality is a guaranteed right for every human being and it is a great basis on which religion is established. God made piety as the balance of prederence between human beings. Islam determined precisely all rights and freedoms by God’s commands and His limits which do not,as some claim , fetters which tie up the energies of the human being and kill his aspirations and his yearnings. Islam supports positive opposition and considers it under commanding good acts and prohibiting abominable acts as a collective duty on the Muslim person, rather it is one of the basic rights which is represented in the freedom of giving opinion within the limits of Sari’a ( Muslim religious law ) and its controls. The study also concluded that the human being in the Islamic conceptualization enjoys rights and freedoms but in the framework of the concept of the appointment of man as God’s successor on the earth (al-istikhlaaf) and slavery to Almighty God, whereas the Western conceptualization gives a free rein to man without a restriction or a condition.